2020
DOI: 10.3389/fpsyg.2020.00697
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Difficulties Are Not Always Associated With Negative Outcomes on Women: The Buffer Effect of HRV

Abstract: The Heart Rate Variability (HRV) is regularly associated with depression and trait emotion regulation. However, the interaction between HRV and emotional disturbances is still debated. Only a few studies indicate that HRV moderates the effect of personality traits involved in psychopathological disorders. Since the regulation of emotions is a transdiagnostic factor for most psychological disorders, this study aimed to explore whether HRV moderates the relationship between trait emotion dysregulation and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(72 reference statements)
2
3
1
Order By: Relevance
“…In our sample, vagally mediated HRV was protective when examining depressive symptoms and followed a similar pattern, though the interaction overall was not significant, for perceived stress. These results are consistent with findings from other research groups that higher vagally mediated HRV reduces or eliminates effects of expressive suppression on negative affect during conflict (Geisler and Schröder-Abé, 2015), enables people to spontaneously suppress negative facial expressions in an adaptive and socially appropriate manner when exposed to a negative film clip (Pu et al, 2010), and protects against depressive symptoms for those with emotion regulation difficulties (Fantini-Hauwel et al, 2020). Although meta-analytic results indicate only a small correlation between self-regulation and HRV (Holzman and Bridgett, 2017), these results may be interpreted as an interplay between this bio-marker of one's self-regulatory ability and the frequency participants report using expressive suppression.…”
Section: Discussionsupporting
confidence: 91%
“…In our sample, vagally mediated HRV was protective when examining depressive symptoms and followed a similar pattern, though the interaction overall was not significant, for perceived stress. These results are consistent with findings from other research groups that higher vagally mediated HRV reduces or eliminates effects of expressive suppression on negative affect during conflict (Geisler and Schröder-Abé, 2015), enables people to spontaneously suppress negative facial expressions in an adaptive and socially appropriate manner when exposed to a negative film clip (Pu et al, 2010), and protects against depressive symptoms for those with emotion regulation difficulties (Fantini-Hauwel et al, 2020). Although meta-analytic results indicate only a small correlation between self-regulation and HRV (Holzman and Bridgett, 2017), these results may be interpreted as an interplay between this bio-marker of one's self-regulatory ability and the frequency participants report using expressive suppression.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, no moderation or mediation effect of HRV on the relationships between emotion regulation and mental health was observed. This is contradictory to previous studies [53,54] showing a protective role of HRV on these relationships. However, all these studies do not rely on clinical populations suffering from cardiac diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in line with previous studies that demonstrated the role of higher HRV levels in protecting individuals who habitually used maladaptive emotion regulation strategies from the development of psychological disorders (e.g. 94 ). This data is relevant because it underlies the importance of combining self-report psychological measures with psychophysiological measures in the assessment of PTSS risk.…”
Section: Discussionsupporting
confidence: 92%